Mechanical aberrations in hypetrophic cardiomyopathy: emerging concepts - Ntelios, Dimitrios; Tzimagiorgis, Georgios; Efthimiadis, Georgios K.; Karvounis, Haralambos (Frontiers in Physiology, 2015)
Hypertrophic cardiomyopathy is the most common monogenic disorder in cardiology. Despite important advances in understanding disease pathogenesis, it is not clear how flaws in individual sarcomere components are responsible for the observed phenotype. The aim of this article is to provide a brief interpretative analysis of some currently proposed pathophysiological mechanisms of hypertrophic cardiomyopathy, with a special emphasis on alterations in the cardiac mechanical properties.